2020
DOI: 10.1200/jco.19.01535
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Genotype Predicts Tamoxifen Discontinuation and Prognosis in Patients With Breast Cancer

Abstract: PURPOSE To examine the association between CYP2D6 genotype, discontinuation of tamoxifen therapy, and prognosis for breast cancer. PATIENTS AND METHODS We conducted a prospective-retrospective study linking data from a clinical breast cancer register, the Swedish Prescribed Drug Register, and self-reported questionnaires. We genotyped CYP2D6 in 1,309 patients with breast cancer who were treated with tamoxifen and were diagnosed from 2005 to 2012; they were categorized as poor, intermediate, normal, or ultrarap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 41 publications
0
41
1
Order By: Relevance
“…30 More evidence for a concentration-dependent risk of adverse effects to the standard dose of tamoxifen comes from recent Swedish data, showing that patients genotyped as CYP2D6 UM, and thereby expected to have higher endoxifen levels at the standard dose of tamoxifen 31 seemed to experience more severe side effects 29,32 and that this would increase the risk of early treatment discontinuation during the first 6 months. 29 Our study has some important limitations. We believe that the obvious limitation of this study is the limited size, and therefore many of our statistically significant findings will require confirmation in larger study settings.…”
Section: Discussionmentioning
confidence: 99%
“…30 More evidence for a concentration-dependent risk of adverse effects to the standard dose of tamoxifen comes from recent Swedish data, showing that patients genotyped as CYP2D6 UM, and thereby expected to have higher endoxifen levels at the standard dose of tamoxifen 31 seemed to experience more severe side effects 29,32 and that this would increase the risk of early treatment discontinuation during the first 6 months. 29 Our study has some important limitations. We believe that the obvious limitation of this study is the limited size, and therefore many of our statistically significant findings will require confirmation in larger study settings.…”
Section: Discussionmentioning
confidence: 99%
“…This was significantly higher than the discontinuation rate of NMs (6.7%) [ 78 ]. At the same time point, no significant difference in tamoxifen discontinuation was found for PMs (7.1%) or IMs (7.6%), as compared to NMs (6.7%) [ 78 ].…”
Section: Factors Affecting Endoxifen Levelsmentioning
confidence: 96%
“…Multivariate analyses showed that about 47% of tamoxifen plasma concentration variability is explained by patient adherence behavior; in addition, the combination of CYP2D6 genotype and adherence behavior explained 40% of endoxifen plasma concentration variability at 12 months [71]. He et al [78] investigated the relationship between CYP2D6 metabolizer status and tamoxifen discontinuation in a prospective-retrospective study, showing that UMs had a discontinuation rate of 18.8% at 6 months after the start of tamoxifen treatment. This was significantly higher than the discontinuation rate of NMs (6.7%) [78].…”
Section: Patient Therapy Adherence and Endoxifen Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are data suggesting that despite the enhanced activation of TAM to END in patients with UM status, this status is linked to a higher intake of symptom-relieving drugs (antinausea, anxiolytics, medications for relief from hot flushes), a higher frequency of early treatment discontinuation, and a worse prognosis for breast cancer compared to extensive metabolizers. 25 …”
Section: Discussion and Decision-makingmentioning
confidence: 99%